ГЕОРАДАРЫН (GPR) –ИЙН ТАНДАН СУДАЛГААГААР ИДЭВХИТЭЙ ХАГАРЛЫН ПАРАМЕТРҮҮДИЙГ НАРИЙВЧЛАХ НЬ - Ц., Нямбаяр; Bano, Maksim; Х., Цээдулам (Geological Issues, 2022)
Seismic activity around the capital city of Ulaanbaatar has been increasing significantly since 2005. This activity is observed in the vicinity of Emeelt and is located at just over 10 km from the residential area of Ulaanbaatar, which is a high risk. As part of the seismic activity survey near Ulaanbaatar, we identified several active faults and began to study them in detail in 2010 year. The length and geomorphology of these active faults indicate a strong earthquake of magnitude 6.5-7.5. After the Paleo-earthquake, the loose soil around the fault has undergone a process of geological erosion, which has significantly altered the traces and geomorphology of the faults on the soil of the fault plane. Therefore, the GPR sensing method for determining the fault parameters in detail, mapping and reconfiguration technology has been tested and proven to be widely used in the future. In 2010-2019, we conducted detailed GPR surveys on active faults around Ulaanbaatar and in the central region to accurately determine their parameters. This article presents the results of using GPR 250MHz, 500MHz, and 50MHz antenna measurements in combination with differential GPS system measurements to determine how active fault parameters can be accurately determined by their results.